Fun Learning Method in Effecting the Students’ Interest Learning Mathematics - Sriyanti Mustafa; Amaluddin Amaluddin; Nurhaeda Nurhaeda; Vernita Sari; Nur Amalia Zulfatul Jannah (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
This study is based on the low interest of students in learning mathematics. The phenomenon was indicated by the activities of students who are often outside the classroom during mathematics learning, the students do not ask when there is confusing material, the students do not complete the task given, and some students are sleepy during the learning process. These conditions indicated a low level of learning interest. At the same time, interest is crucial in learning mathematics because it affects students' learning achievement. Regarding the condition, the teacher's role is to increase the student's learning interest by applying appropriate methods. One of the learning methods that is assumed to be able to attract students' learning interest is the fun learning method. The fun learning method in this study was applied through classroom action research with two learning cycles. This study aims to know the effect of fun learning methods on students' interest in mathematics. This study was conducted at VII.7 grade of SMP Negeri 1 Pinrang, South Sulawesi. The research instrument used was a questionnaire and an observation sheet. The data was collected through a questionnaire and observation, then the data collected was analysed using descriptive statistics. Indicators of increased interest obtained from questionnaires show an increase in the average percentage of student interest in learning from the moderate category of 2.88 to the good category of 4.08, which meets the average indicator of students' interest in learning mathematics of 3.50 in the good category. In contrast, other indicators are shown through the results of observations of student activity, namely an increase in the percentage of student activity from 44.2% to 75.4%, which met the success indicator of 75%. The result showed that the fun learning method could increase the student's interest in mathematics.Penelitian ini berawal dari rendahnya minat siswa belajar matematika. Gejala ditunjukkan adanya aktivitas siswa yang sering berada di luar kelas pada saat pembelajaran matematika berlangsung, siswa tidak bertanya ketika ada hal yang tidak diketahui pada materi yang diajarkan guru, siswa tidak mengerjakan soal-soal yang diberikan, serta beberapa siswa mengantuk saat pembelajaran matematika berlangsung. Kondisi ini mengindikasikan minat belajar yang rendah. Padahal peran minat sangat penting dalam pembelajaran matematika, karena merupakan faktor yang berpengaruh terhadap hasil belajar siswa. Dengan kondisi tersebut, maka dibutuhkan peran guru dalam meningkatkan minat belajar siswa dengan menerapkan metode yang tepat. Salah satu metode pembelajaran yang diasumsikan dapat menarik minat belajar siswa adalah metode fun learning. Metode fun learning dalam penelitian ini diterapkan melalui penelitian Tindakan kelas sebanyak dua siklus pembelajaran. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan metode fun learning yang dapat meningkatkan minat belajar matematika siswa. Penelitian dilakukan dikelas VII7 SMP Negeri 1 Kabupaten Pinrang, Sulawesi Selatan. Instrumen penelitian yang digunakan berupa lembar angket dan lembar observasi. Data dikumpulkan melalui teknik angket dan teknik observasi, selanjutnya dianalisis secara statistic deskriptif. Indikator peningkatan minat yang diperoleh dari angket menunjukkan meningkatnya persentase rata-rata minat belajar siswa dari kategori cukup sebesar 2.88 menjadi kategori baik sebesar 4.08, memenuhi indikator rata-rata minat belajar matematika siswa sebesar 3,50 berada pada kategori baik, sedangkan indikator lain ditunjukkan melalui hasil observasi aktivitas siswa, yaitu meningkatnya persentase aktivitas siswa sebesar 44.2% menjadi 75.4%, memenuhi indikator keberhasilan sebesar 75%. Hasil penelitian menunjukkan bahwa metode Fun learning dapat meningkatkan minat siswa belajar matematika.